Transformations in Maritime Transport in the Digital Age: A Legal Study of the Electronic Bill of Lading in the United Arab Emirates - Alkindi, Amna; Kisswani, Nazzal (Journal of Legal Sciences, 2026)
This research addresses the nature of electronic bills of lading in light of Emirati legislation, by defining, describing its functions, mechanisms, establishment, parties involved, and its significance as a new means of proving maritime transport contracts. It also discusses the substantive and formal conditions of such documents, with the research problem lying in the absence of national legislative rules regulating them, and the adequacy of the provisions of )the Electronic Transactions and Trust Services Law No. (46) for the year 2021( in addressing them in the UAE, along with the UAE Maritime Trade Law. The research adopts an analytical and comparative approach and consists of a set of findings, among which are:• The role of electronic bills of lading has evolved to become a tool for proving both transport and shipping contracts, culminating in being a credit instrument representing the goods. Therefore, possessing it indicates possession of the goods, resulting in the same legal consequences as possession of the goods themselves.• Both traditional and electronic bills of lading serve the same purpose, and electronic maritime bills of lading can perform the same role as traditional bills of lading in proving contractual transactions.